Education and Counselling for Promiscuity at SMA Negeri 1 Limboto - Sabirin B. Syukur; Nirmala Sunati; Rini Asnawati; Melisa Dwi Wulandari Sione; Diki Adik Putra Suaib (Universitas Muhammadiyah Palu, 2026)
Background: Promiscuity in adolescents is one of the problems that can have a negative impact on students' health, social, and psychological development. Lack of knowledge about promiscuity makes adolescents more susceptible to being influenced by the environment and risky behaviors. Therefore, educational efforts are needed to increase students' understanding and awareness of the importance of healthy associations. Objective: This activity aims to increase the knowledge and understanding of SMA Negeri 1 Limboto students about promiscuity, the forms of behavior included in it, the causative factors, the impact caused, and efforts to prevent it. Methods: Activities are carried out through the stages of study, planning, implementation, and evaluation. The assessment method used observation of students of SMA Negeri 1 Limboto. Education is provided through health counseling using PowerPoint (PPT) media and interactive discussion methods to increase student participation in the learning process. Results: The results of the activity showed that before the counseling most students had a low level of knowledge about promiscuity. After the implementation of education, there is an increase in student understanding which is shown by the ability to re-explain the meaning of promiscuity, causative factors, negative impacts, and how to avoid it. Students also show high activity during the discussion process and have a better awareness of the importance of maintaining healthy social behavior. Conclusion: Education and counseling regarding promiscuity have proven to be effective in increasing the knowledge and awareness of SMA Negeri 1 Limboto students. Discussion methods supported by visual media are able to create an interactive learning process and improve student understanding. Ongoing health education activities are needed to help adolescents develop healthy, responsible behavior, and avoid the negative effects of promiscuity.